Improving access to genetic testing for adults with intellectual disability: A literature review and lessons from a quality improvement project in East London. Issue 8 (11th May 2019) - Adlington, Katherine; Smith, James; Crabtree, Jason; Win, Soe; Rennie, Jade; Khodatars, Kuresh; Rosser, Elisabeth; Hall, Ian
Abstract: Recent advances in genetic research have led to an increased focus on genetic causes of intellectual disability (ID) and have raised new questions about how and when clinicians offer genetic testing and the nature of communication around this decision with patients and carers. Determining the right approach to such discussions is complicated by complexities of communication, consent, and capacity and ethical concerns about genetic testing in this population. In this article, we briefly discuss the recent advances in genetic research relevant to people with intellectual disability, highlighting the challenges that might arise when undertaking genetic testing in this population. We then describe how we have used a Quality Improvement methodology to develop a clinical pathway for routine genetic testing for adults with intellectual disability in a clinical setting in East London.